2015
DOI: 10.1093/jat/bkv079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolite Biomarkers of the Designer Hallucinogen 25I-NBOMe in Mouse Hepatic Microsomal Preparations and Human Urine Samples Associated with Clinical Intoxication

Abstract: 'NBOMe' (dimethoxyphenyl-N-[(2-methoxyphenyl)methyl]ethanamine) derivatives are a new class of designer hallucinogenic drugs widely available on the Internet. Currently, 2-(4-iodo-2,5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25I-NBOMe) is the most popular abused derivative in the USA. There are little published data on the absorption, metabolism and elimination of 25I-NBOMe, or any of the other NBOMe derivatives. Therefore, there are no definitive metabolite biomarkers. We present the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 18 publications
3
31
2
Order By: Relevance
“…The metabolism of 25I‐NBOMe has recently been considered in several in vivo studies . Caspar et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolism of 25I‐NBOMe has recently been considered in several in vivo studies . Caspar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Poklis et al identified one main monohydroxylated metabolite of 25I‐NBOMe in the two cases included in their study, but lacking primary reference standards, it was not possible to determine the exact location of the hydroxylation. They were able to determine that the hydroxylation was located at the methoxybenzyl moiety based on the fragmentation pattern . Our results support their identification, and using a reference standard exact location of the main monohydroxylated metabolite was determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that in one case we did not detect 25I-NBOMe in urine from an intoxicated patient collected 13 hours post-admission. Four O-desmethyl metabolites were the only 25I-NBOMe analogs detected (5). With the exception of 2CT-NBOMe, 2-[2,5 dimethoxy-4-(methylthio) phenyl]-N-(2-methoxybenzyl)ethanamine, which is unstable in urine at room temperature, we have found NBOMe derivatives are stable in urine at room temperature for 3 days and frozen for at least one month (6).…”
Section: To the Editormentioning
confidence: 99%